THE EFFECT OF INTERNAL COMMUNICATION TO THE EMPLOYEE PERFORMANCE IN THE FACULTY SOCIAL AND POLITICAL SCIENCE UNIVERSITY OF ISLAMIC BALITAR-BLITAR - Nuryanti Nuryanti (Universitas Islam Balitar, 2022)
The study intends to determine how the influence of internal communication on employee performance at the Faculty of Social and Political Sciences, Islamic University of Balitar-Blitar. This research was conducted using quantitative methods with a sample of 35 employees To measure the results of the validity of the instrument using validity and reliability tests. Then test the classical assumptions by testing normality and heteroscedasticity. Hypothesis test using T test (partial test). The results of the study show that internal communication has a significant effect on employee performance with the significance value is 0.014. Based on the data of this reasearch result, it is expected that the leadership will conduct meetings more often so that communication can run more smoothly and there is no misunderstanding of information due to lack of coordination.